An investigation of nanostructured thin film Î±-MoO3 based supercapacitor electrodes in an aqueous electrolyte - MENDOZA SANCHEZ, BEATRIZ; NICOLOSI, VALERIA (My University, 2013)
The potential for MoO3 use as a supercapacitor electrode in aqueous electrolytes was investigated. α-MoO3 nanobelts were synthesized using a hydrothermal method and then thin-film electrodes were manufactured by spray deposition. Electrochemical testing in several aqueous electrolytes showed significant charge storage in 1 M H2SO4 with a complex electrochemical activity that was further investigated by X-ray photoelectron spectroscopy and various electrochemical characterization methods. In a 0–1 V (vs Ag/AgCl) electrochemical window, MoO3 was reduced to a mixture of lower valence oxides with concentrations varying as Mo (5+) > Mo (4+) > Mo (6+), with MoO2 as the main component at potentials below 0.185 V (vs Ag/AgCl). The degree of redox reversibility was evaluated in order to optimize the electrochemical window for enhanced cyclability. A moderate capacitance of 8.8 F g−1 (64 μF cm−2) was fully retained for 720 cycles in an optimized electrochemical window of 0.26–0.43 V (vs Ag/AgCl).
PUBLISHED
Keywords: Cyclability; Capacitance; Redox activity; Supercapacitors; α-MoO3 nanobelts